Authenticity of authorship of scientific publications using latent semantic analysis - Коляда, Андрей Сергеевич; Гогунский, Виктор Дмитриевич (Eastern-European Journal of Enterprise Technologies, 2014)
In this research, a latent semantic analysis is used to solve the problem of identifying authorship of scientific publications. It enables the identification of keywords related to a particular subject. It is proposed to use the keywords for identifying similar publications. This allows distinguishing publications of different authors with the same last names or even initials. Many scientometric databases contain records of publications with the same field “author”, but with completely different activities, sources, etc. As a result of the studies, it was found that publicationsof namesakes have a different set of keywords and, accordingly, different subject-matters. Applying the latent semantic analysis can be used to classify these publications, as well as highlighting the keywords, which bind to the author, in turn, enables determining his publications with some accuracy. The research results allow automating the creation of local databases of researchers with a list of their scientific papers.